A review on the effect of seed moisture on germination of rubber seed / Muhammad Akmal Rosli - Rosli, Muhammad Akmal (Faculty of Plantation and Agrotechnology, 2019)
Seeds are important for plants to produce their offspring and also important for cultivation. Since the demand for natural rubber is increasing, there is opening of new rubber plantations. The studies on rubber seed storage behaviour, factor contributing to emergence of rubber seeds, and moisture content (MC) are needed for germination. Such studies can help growers or farmers for establishment of their field. Rubber seeds are categorized as intermediate seed behaviour which is partial desiccation tolerant. Rubber seed is seasonal as the tree only produces fruit twice a year, i.e. in February to March and August to September. Rubber seeds are usually used as rootstock for new planting materials. High quality seeds are important for seedling development as rootstock because it will affect the growth, disease tolerance and yield. Studies on seed dispersal and the associated processes of germination, seedling establishment and survival are important for understanding plant regeneration dynamics and dispersal ability, especially for introduced plant species like rubber. For germination of rubber seeds, favourable conditions are needed. The optimum temperature for rubber seeds to germinate is 28°C at relative humidity of >35%. Studies on rubber seed germination after storage are also important to avoid the seed deterioration. Rubber seeds cannot withstand sunlight exposure because it decreases the MC of seeds. Rubber seeds are also sensitive to chilling injury. Storage of seeds is important because it can help farmers to keep the viability of seeds to be used for future purpose.